ANALISIS IMPLEMENTASI PERATURAN PRESIDEN NOMOR 9 TAHUN 2016 TENTANG PERCEPATAN PELAKSANAAN KEBIJAKAN SATU PETA PADA TINGKAT KETELITIAN PETA SKALA 1 : 50.000 (Studi Pada Kantor Pertanahan Kabupaten Lampung Utara) - S. Endang Prasetyawati; DESLAPANA DESLAPANA (Universitas Bandar Lampung (UBL), 2021)
Land conflicts that often occur are caused by misalignment in land administration. Land administration services have not supported the availability ofvalid and accurate data, for example an area is claimed to be a forest area, but empirical facts in the area have become settlements. This is where the importance of land administration, because good land administration will eliminate social inequalityin society. The problem in this research is how is the implementation of PresidentialRegulation Number 9 of 2016 concerning the Acceleration of the Implementation of theOne Map Policy at the Map Accuracy Level of 1: 50,000 Scale? What are the obstaclesin the implementation of Presidential Regulation Number 9 of 2016 concerning theAcceleration of the Implementation of the One Map Policy at the Level of MapAccuracy (Scale 1: 50,000 at the Land Office of North Lampung Regency)? Theresearch method used is a normative juridical approach and an empirical approach, thedata used are secondary data and primary data with qualitative analysis in order toobtain a correct and objective research result. The results of the research are theimplementation of Presidential Regulation Number 9 of 2016 concerning theAcceleration of the Implementation of the One Map Policy at the Level of MapAccuracy Scale 1: 50,000 At the Land Office of North Lampung Regency currently ithas been implemented but has not run optimally, Barriers to the implementation ofPresidential Regulation Number 9 of 2016 concerning Acceleration of One Map Policy Implementation at the Level of Map Accuracy Scale 1: 50,000 In North Lampung Regency, which is still not optimal counseling and socialization to the public about theOne Map Policy in North Lampung Regency. One Map in North Lampung Regency, Theauthor's suggestion is for the Land Office of North Lampung Regency in order toimprove coordination, synergy and cooperation with all relevant stakeholders so thatthe implementation of the One Map Policy in North Lampung Regency can be carriedout properly and maximally.